Fountain of youth—Targeting autophagy in aging - Danics, Lea; Abbas, Anna Anoir; Kis, Balázs; Pircs, Karolina (Frontiers in Aging Neuroscience, 2023)
As our society ages inexorably, geroscience and research focusing on healthy aging is becoming increasingly urgent. Macroautophagy (referred to as autophagy), a highly conserved process of cellular clearance and rejuvenation has attracted much attention due to its universal role in organismal life and death. Growing evidence points to autophagy process as being one of the key players in the determination of lifespan and health. Autophagy inducing interventions show significant improvement in organismal lifespan demonstrated in several experimental models. In line with this, preclinical models of age-related neurodegenerative diseases demonstrate pathology modulating effect of autophagy induction, implicating its potential to treat such disorders. In humans this specific process seems to be more complex. Recent clinical trials of drugs targeting autophagy point out some beneficial effects for clinical use, although with limited effectiveness, while others fail to show any significant improvement. We propose that using more human-relevant preclinical models for testing drug efficacy would significantly improve clinical trial outcomes. Lastly, the review discusses the available cellular reprogramming techniques used to model neuronal autophagy and neurodegeneration while exploring the existing evidence of autophagy’s role in aging and pathogenesis in human-derived in vitro models such as embryonic stem cells (ESCs), induced pluripotent stem cell derived neurons (iPSC-neurons) or induced neurons (iNs).